2016
DOI: 10.1617/s11527-016-0828-2
|View full text |Cite
|
Sign up to set email alerts
|

Dam and wet-screened concrete creep in compression: in situ experimental results and creep strains prediction using model B3 and composite models

Abstract: This paper proposes a methodology for the prediction of the compressive creep strains of dam concrete based on wet-screened experimental results at constant elevated temperature conditions measured in situ. Due to its large aggregate dimensions, the experimental characterization of dam concrete has particular constraints. The wet-screened concrete, obtained by sieving the aggregates larger than a given dimension, after mixing, is used to cast standard specimens and to embed monitoring devices. An experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…On the whole, it can be concluded that the increase of the specimen size does result in the variations of the macroscopic mechanical parameters related to tensile fracturing behaviors, which is consistent with the existing research results concerning the size e ect of concrete [38]. However, in view of the large variation amplitudes of the investigated parameters obtained by limited experimental studies [11] (e.g., the typical ratio of the tensile strength of HFGC specimen to that of the corresponding wet-screened concrete specimen is ranging from 0.65 to 0.85), the variation of the specimen size is not a governing factor. Figures 11 and 12 illustrate the variations of CoVs of tensile elastic modulus, peak stress, peak strain, and fracture energy with the sample number for Types I and II, respectively, from which it is noted that 50 random specimens are enough to achieve statistical convergence.…”
Section: E Ect Of Specimen Sizesupporting
confidence: 89%
See 1 more Smart Citation
“…On the whole, it can be concluded that the increase of the specimen size does result in the variations of the macroscopic mechanical parameters related to tensile fracturing behaviors, which is consistent with the existing research results concerning the size e ect of concrete [38]. However, in view of the large variation amplitudes of the investigated parameters obtained by limited experimental studies [11] (e.g., the typical ratio of the tensile strength of HFGC specimen to that of the corresponding wet-screened concrete specimen is ranging from 0.65 to 0.85), the variation of the specimen size is not a governing factor. Figures 11 and 12 illustrate the variations of CoVs of tensile elastic modulus, peak stress, peak strain, and fracture energy with the sample number for Types I and II, respectively, from which it is noted that 50 random specimens are enough to achieve statistical convergence.…”
Section: E Ect Of Specimen Sizesupporting
confidence: 89%
“…Although the wet-screening method can avoid the direct testing on large specimens, a gap inevitably exists [9] between the real mechanical parameters of HFGC specimens and those of the corresponding wet-screened specimens; that is, the standard specimens cast using the wet-screened concrete. erefore, an extrapolation procedure should be executed with the aim of acquiring the accurate characterization of the mechanical properties of HFGC [10], which necessitates a detailed comparative study on the mechanical parameters of hydraulic fully graded and wet-screened concretes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Dam concrete is mass concrete with a poor binder content (100-300 kg/m 3 ) and wet-screened concrete is obtained by removing the larger aggregates from the original concrete mix. 1 The presence of free water in the micropores of a long-term hydraulic-concrete structure produces expansion pressure and seepage pressure in freeze-thaw cycles due to the alternating action of positive and negative temperatures. This reaction can be both periodic and nonperiodic, leading to significant changes in the mechanical and thermal properties of the structure and eventually to catastrophic fatigue damage to the structure.…”
Section: Introductionmentioning
confidence: 99%
“…strength are affected by the number of freeze-thaw cycles, the current freeze-thaw test research of concrete mainly follows industry-related norms and standards. According to the Chinese code GB/T 50082-2009, 2 a freeze-thaw test is completed when one of the following conditions is met: (1) the number of freeze-thaw cycles reaches a specified value, (2) the relative dynamic modulus of elasticity decreases to 60% of the initial value, or (3) the mass-loss rate reaches 5%. According to ASTM C666-03, 3 however, such tests must continue until each specimen has undergone 300 cycles or until its relative dynamic modulus of elasticity decreases to 60% of the initial value.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation